2013
DOI: 10.2478/s11696-012-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous dehydrochlorination of 1,3-dichloropropan-2-ol to epichlorohydrin: process parameters and by-products formation

Abstract: The influence of pre-reactor and reactor temperatures on the conversion of 1,3-dichloropropan-2-ol and the selectivity of its transformation to epichlorohydrin in continuous dehydrochlorination for two modes of the reaction product collection was studied. The dehydrochlorination process and mechanism of diglycidyl ether formation are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The ET was present in both the distillate and wastewater at the highest molar ratio. In other studies, we have shown that it forms in the reaction EPI with DCP. The selectivity of transformation to the polyethers is a supplementation of the selectivity of transformation to the organic compounds (Table S2) to 100%.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The ET was present in both the distillate and wastewater at the highest molar ratio. In other studies, we have shown that it forms in the reaction EPI with DCP. The selectivity of transformation to the polyethers is a supplementation of the selectivity of transformation to the organic compounds (Table S2) to 100%.…”
Section: Resultsmentioning
confidence: 63%
“…In our research, the dehydrochlorination agent is an aqueous solution of calcium hydroxide. The dehydrochlorination is carried out in the apparatus and according to the method described in a previous paper . A byproduct formed in this process, and the influence of prereactor temperature on the conversion of 13DCP2OL and the selectivity of transformation to EPI using different methods of product collection were also presented in the mentioned paper.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the reactive mixtures was studied [97], concluding that 1,2-DCH is much less reactive than 1,3-DCH, although primary alkyl alcohols are more acidic than secondary alkyl alcohols. The influence of the reactor on the reaction kinetics [98,99] and of the cation on the 1,3-DCH dehydrochlorination [59,61,97,100] was also studied.…”
Section: Chemical Synthesis Of Echmentioning
confidence: 99%
“…This causes not only the corrosion of the reaction equipment but also generates a large amount of by‐products and waste liquid. Besides, there are many problems with refining the main products and separating the catalysts from the reaction mixture . Compared with homogeneous catalysis, solid catalysis enables easier product separation, hence avoiding the production of large volumes of wastewater and increasing the cost efficiency, using less labor materials and financial resources …”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are many problems with refining the main products and separating the catalysts from the reaction mixture. [8][9][10] Compared with homogeneous catalysis, solid catalysis enables easier product separation, hence avoiding the production of large volumes of wastewater and increasing the cost efficiency, using less labor materials and financial resources. [11][12][13][14] A solid base is a substance that can donate electron pairs or accept protons.…”
Section: Introductionmentioning
confidence: 99%